Full scale experiments on splitting behaviour of concrete slabs in steel concrete composite beams with shear stud connection. (February 2020) - Lowe, Daniel; Roy, Krishanu; Das, Raj; Clifton, Charles G.; Lim, James B.P.
Abstract: This paper presents the results of 15 push-off tests to determine, with a high degree of precision, the longitudinal splitting characteristics of a concrete slab in a novel steel-concrete composite beam with headed shear stud connectors. A modified test rig was developed, instead of the standard push-off test rigs. Both monotonic and cyclic loadings were considered. The experiments allowed the exploration of several currently unknown effects of various loads on components of steel-concrete composites, such as transverse loading and low-level cyclic loading on shear stud capacity. The results allowed the splitting failure mode to be characterised in unprecedented detail. It was found that for the case of cyclic loading, when many cycles were applied, it did not lead to premature failure of the composite beam, but instead increased the capacity of the beam against longitudinal splitting. This is significant for composite members under variable loading, such as floor supporting beams in car parks. It was also shown that the transverse compression forces across the base of the studs would increase the capacity of the beam against longitudinal splitting. Also studied were the differences and limitations of EuroCode 4 and New Zealand (NZS) standards and their effects on composite beam failure characteristics. It was shown that the presence of anti-splitting reinforcement would result in a gradual loss of load carrying capacity, compared to a sudden loss when not present. Even with sufficient side cover from the stud to the edge of the concrete, following the NZS standard, longitudinal splitting in composite beams continues to be observed.